2008
DOI: 10.7589/0090-3558-44.2.247
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Oral and Parenteral Routes of Mycobacterium Bovis Bacille Calmette-Guerin Vaccination Against Experimental Bovine Tuberculosis in White-Tailed Deer (Odocoileus Virginianus): A Feasibility Study

Abstract: We investigated the efficacy of oral and parenteral Mycobacterium bovis bacille Calmette-Guerin Danish strain 1331 (BCG) in its ability to protect white-tailed deer (Odocoileus virginianus) against disease caused by M. bovis infection. Twenty-two white-tailed deer were divided into four groups. One group (n=5) received 10(9) colony-forming units (cfu) BCG via a lipid-formulated oral bait; one group (n=5) received 10(9) cfu BCG in culture directly to the oropharynx, one group (n=6) was vaccinated with 10(6) cfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
78
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(91 citation statements)
references
References 24 publications
5
78
1
Order By: Relevance
“…An edible lipid matrix has been developed that allows BCG bacilli to be maintained in a viable but static state that is suitable as an oral delivery vehicle for the vaccine (Aldwell et al 2005). Studies in a range of animal species have shown that oral vaccination with this lipid-formulated BCG can induce a level of protection against experimental challenge with Tb that is comparable with that induced by injecting the vaccine (Aldwell et al 2003a,b;Buddle et al 2006;Nol et al 2008). However, vaccination has generally not prevented animals from becoming infected as a result of experimental challenge; rather, it has slowed the progression of the disease relative to that in unvaccinated animals, as shown by a reduction in the severity of disease and bacterial counts in lungs and spleen (Aldwell et al 1995(Aldwell et al , 2003aBuddle et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…An edible lipid matrix has been developed that allows BCG bacilli to be maintained in a viable but static state that is suitable as an oral delivery vehicle for the vaccine (Aldwell et al 2005). Studies in a range of animal species have shown that oral vaccination with this lipid-formulated BCG can induce a level of protection against experimental challenge with Tb that is comparable with that induced by injecting the vaccine (Aldwell et al 2003a,b;Buddle et al 2006;Nol et al 2008). However, vaccination has generally not prevented animals from becoming infected as a result of experimental challenge; rather, it has slowed the progression of the disease relative to that in unvaccinated animals, as shown by a reduction in the severity of disease and bacterial counts in lungs and spleen (Aldwell et al 1995(Aldwell et al , 2003aBuddle et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Vaccination of WTD with the M. bovis BCG strain Danish (20) or BCG strain Pasteur (23) has been shown to be efficacious as measured by a reduction in pathology (24). To deter-mine T-cell-mediated responses induced by vaccination with these BCG strains and to correlate these responses to protection/pathology, WTD were vaccinated with either BCG Danish or BCG Pasteur and subsequently infected with virulent M. bovis.…”
mentioning
confidence: 99%
“…Deer consuming numerous baits not only decreases the remaining number of baits and negatively impacts vaccine coverage but also results in ingestion of a greater than desired dose of BCG by eager deer. According to Nol et al (2008), an oral dose of 10 9 CFUs provides protection to experimentally infected deer. It is not clear what effect high BCG dosages have on vaccine efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Delivery of the ONRAB(®) vaccine in baits has been used widely across the USA and Canada to control rabies in raccoons (Procyon lotor) (Roess et al 2012, Slate et al 2009). Experimentally, oral vaccination of white-tailed deer with the human vaccine, bacillus Calmette-Guerin (BCG), an attenuated strain of M. bovis, effectively reduces the severity of disease upon challenge with virulent M. bovis (Palmer et al 2007;Nol et al 2008). Oral vaccination of deer with BCG represents a possible control strategy in areas of highest prevalence, to reduce deer-to-deer and deer-to-cattle transmission of M. bovis.…”
Section: Communicated By C Gortázarmentioning
confidence: 99%
See 1 more Smart Citation